Pengaruh Desain Produk, Perceived Quality, dan Persepsi Harga Terhadap Keputusan Pembelian Sepatu Merek Adidas di Surabaya - Yuan Adi Pratama; I.A. Nuh Kartini (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
The aim of this study is to analyze the effects of perceived quality, product design, and price perception on the purchase decision of Adidas brand shoes. In this study, a questionnaire was distributed, and a quantitative approach was used through multiple regression analysis. The results showed that while product design does not have a significant impact on purchase decisions, perceived quality and price perception have a significant influence on purchase decisions. Therefore, perceived quality and price appropriateness have a significant impact on students' decisions to purchase Adidas shoes. Furthermore, these three variables all play an important role in determining consumer decisions. Therefore, companies need to enhance product quality and lower prices to reflect perceived value.